2020
DOI: 10.3389/fonc.2020.506739
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Cardiac MRI in Breast Cancer Survivors After Cardiotoxic Chemotherapy and Three-Dimensional Conformal Radiotherapy

Abstract: Purpose/Objectives: Node-positive breast cancer patients often receive chemotherapy and regional nodal irradiation. The cardiotoxic effects of these treatments, however, may offset some of the survival benefit. Cardiac magnetic resonance (CMR) is an emerging modality to assess cardiac injury. This is a pilot trial assessing cardiac damage using CMR in patients who received anthracycline-based chemotherapy and three-dimensional conformal radiotherapy (3DCRT) regional nodal irradiation using heart constraints. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 80 publications
0
27
0
Order By: Relevance
“…LVEF stayed within normal limits in multiple studies. In 20 breast cancer patients who received 3D conformal RT (3DCRT), a median LVEF of 63% was reported at 8.3 years [45]. Similar ndings were noted for 5 HL survivors who underwent chemotherapy and proton RT with LVEF of 60% at 5 years post treatment [49].…”
Section: Iia2 Lvef Unchangedmentioning
confidence: 52%
See 2 more Smart Citations
“…LVEF stayed within normal limits in multiple studies. In 20 breast cancer patients who received 3D conformal RT (3DCRT), a median LVEF of 63% was reported at 8.3 years [45]. Similar ndings were noted for 5 HL survivors who underwent chemotherapy and proton RT with LVEF of 60% at 5 years post treatment [49].…”
Section: Iia2 Lvef Unchangedmentioning
confidence: 52%
“…Changes in other global metrics, such as global strain, have been shown to precede LVEF changes [69], with the earliest changes being noted over shorter follow-ups (e.g., 13 ± 2 months) in patients undergoing concurrent treatments (e.g., chemoradiotherapy) [52], in which the cardiotoxic effects of chemotherapy and radiotherapy may be compounded. In this review of RT effects assessed with MRI, no dosedependency was observed in global measurements, except for changes in cardiac chamber dimensions in either pediatric patients (e.g., LV diastolic volume correlated with heart/LV dose) over short follow-ups (< 2 years) [55], who are more susceptible to radiation damage [20], or in patients undergoing concurrent treatment over longer follow-ups (e.g., LV mass index correlation with LV mean dose at > 8.3 years) [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No wall motion abnormalities and no LGE were found. Similarly, Bergom et al ( 69 ) find no correlation between the mean heart irradiation dose (4.8 Gy, range 1.1–11.2 Gy) and CMR-derived LV dimensions, LVEF, LV mass, GLS and ECV in 20 breast cancer patients at 8.3 years after anthracycline chemotherapy and regional nodal irradiation with 3DCRT.…”
Section: Multimodality Cardiovascular Imaging In Radiotherapy-induced...mentioning
confidence: 94%
“…A 10, 30, 40, and 116% percentage increases in the rate of major coronary events were demonstrated in women with breast cancer and mean radiation dose to the heart < 2, 2–4, 5–9, or > 10 Gy, respectively ( 3 ). On the other hand, some of the recent studies with modern cardiac imaging techniques have failed to demonstrate significant myocardial injury, questioning the actual cardiotoxicity of modern RT regimens ( 27 , 28 , 69 , 71 ). However, there were several important differences between the outcome and the imaging studies.…”
Section: Gaps In Knowledge and Future Perspectivesmentioning
confidence: 99%